1998
DOI: 10.1164/ajrccm.158.6.9608027
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Airway Closure between Normal and Asthmatic Subjects Measured with Single-Photon Emission Computed Tomography and Technegas

Abstract: The absence of a maximal dose-response plateau as well as gas trapping and increases in closing capacity (CC) suggest that increased airway closure is an important mechanical abnormality of asthmatic airways. We compared the extent and distribution of airway closure in 13 normal and in 23 asthmatic subjects. Airway closure (LVclosed) was measured with single-photon emission computed tomography (SPECT) and an inhaled Technegas bolus as the percentage of lung volume without Technegas (LVtrans), and with CC, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
81
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 25 publications
9
81
1
Order By: Relevance
“…In accordance to the computational models discussed above, this is indicative of a heterogenous pattern of constriction that includes randomly distributed airway closures or near closures (138). These observations are supported by ventilation imaging studies such as hyperpolarized 3 He MRI (39,207,234), single-photon emission computed tomography (116) and positron emission tomography (169). These studies showed that asthmatics have increased ventilation heterogeneity at baseline and, even if heterogeneous airway response to a spamogen is also observed in non-asthmatics, the level of ventilation heterogeneity achieved is greater in asthmatics (39,207,234).…”
Section: Non-uniform Ventilation With Air Trapping and Ahrsupporting
confidence: 73%
“…In accordance to the computational models discussed above, this is indicative of a heterogenous pattern of constriction that includes randomly distributed airway closures or near closures (138). These observations are supported by ventilation imaging studies such as hyperpolarized 3 He MRI (39,207,234), single-photon emission computed tomography (116) and positron emission tomography (169). These studies showed that asthmatics have increased ventilation heterogeneity at baseline and, even if heterogeneous airway response to a spamogen is also observed in non-asthmatics, the level of ventilation heterogeneity achieved is greater in asthmatics (39,207,234).…”
Section: Non-uniform Ventilation With Air Trapping and Ahrsupporting
confidence: 73%
“…Regional patterns of ventilation in asthma have also been explored using inhaled gas contrast agents in conjunction with imaging (11)(12)(13)(14), including hyperpolarized helium-3 magnetic resonance imaging (HP MRI) (15). Like MDCT measures of parenchymal density, whole lung measures of ventilatory defect number on HP MRI correlate with obstructive physiology (7,14,16).…”
Section: Introductionmentioning
confidence: 99%
“…This has been demonstrated for both large (internal diameter >2mm) and small (internal diameter <2mm) airways during induced bronchoconstriction or natural events throughout dynamic imaging of the lungs obtained by using ultrafine radioactive aerosol and SPECT technique [15] or hyperpolarized helium-3 magnetic resonance [16].…”
Section: Pulmonary Function Measurementsmentioning
confidence: 93%